An integrated dyspepsia module for first year Pharmacy students: a flexible and generic template for integrating science with clinical and professional practice - De Matteis, Cristina I.; Randall, Michael D.; Harvey, Eleanor J.; Morris, Andrew; Winkler, G. Sebastiaan; Boardman, Helen F. (American Association of Colleges of Pharmacy, 2017)
Objective: To design an integrated dyspepsia module for first year pharmacy undergraduates, which combines clinical and professional practice with fundamental sciences, in five different science subject areas, as a prototype for future disease- or system-based integrated modules. Methods: The approaches used in designing this module are described with particular emphases on strategies adopted to integrate science and practice, and the new ways of working adopted by the design team. Students’ views and experiences of the module, and its integration, were explored using questionnaires. Results: A high proportion of students reported positive views and experiences of the module, the integration and its impact (as self-reported) on their learning and practice. The assessment of student performance indicated learning and attainment was at an appropriate level for a first year module. Both the student marks and research results indicate a positive student learning experience. The main activities undertaken whilst designing and developing the module, and the personnel involved are presented, and provide an indication of the staff time and resourcing required in developing this module. Conclusions: The dyspepsia module provides a flexible and effective template for the integration of science and practice in theme-based modules, with students reporting positively about the integration, including their perception of its contribution to improving their learning and understanding. Our experience suggests that new more collaborative ways of working are required when designing integrated modules.